Origem e (Trans)Formação Urbana: Metamorfose do Lugar e do Tempo no estudo do espaço paroquial de São Mamede de Infesta - Helena Isabel Neto da Silva (2021)
This dissertation has as a case study the evolution and transformation of the parish space of São Mamede de Infesta, located in the municipality of Matosinhos, a place between land and sea. Today's knowledge of this urban structure, with all its characteristics and potential, was the starting point for its study. The (re)recognition of a place created through the study of its urban and road structure to the way its expectant green spaces form the so-called Green Arc of the city. This notion and recognition of the current green areas was the starting point for the construction of the evolutionary narrative of the parish space, since most of them refer us to the past of agricultural production in this territory. Thus, at first, it is intended to create a kind of preamble for the construction of a narrative, starting from a questioning of the reasons that led primitive man to settle in this place, taking into account topographic, hydrographic and also issues. of the population's livelihood system. From the presence of the Phoenician people in the territory under study to the present day, the aim is to reconstitute the parish space of São Mamede de Infesta since ancient times, noting sociocultural political events that influenced and marked not only the territory at national level but also local. Drawing as a tool for translating our thinking, as a student of architecture, allowed us to create a dialogue between the field of history and the visual field of today in the place under study. Faced with this narrative, an intervention proposal is proposed that goes beyond the visible, searching in the vestiges and memories of the past, the answers to the expectations of future transformation for this place.